"Who's Pitiful Now?": Othering and Identity Shifts of Japanese Youth From California to Tokyo. Issue 1 (2nd January 2019) - Shao-Kobayashi, Satoko
ABSTRACT: This study examines how intraethnic relationships and identities are understood, negotiated, and repositioned among Japanese students at Pearl High School (pseudonym) in California, within a transnational context. I utilize a 2-year multisite ethnography and discourse analysis of follow-up interviews collected over the past 10 years. By focusing on their practices of intraethnic Othering using labels in association to social places, I show the multivocality and multilocality of their identity negotiation as follows: (a) Groups of seemingly homogeneous Japanese students differentiate each other by using labels (e.g. "Jap, " "FOB" (fresh off the boat), "wannabe") and making territories within their school. (b) The Japanese university admission policy for returnees ( kikoku ) situates these students on their return to Japan to renegotiate their identity in between culturally kikoku and institutionally kikoku . (c) The transnational transition into kikoku, while reproducing the underlying ideologies, twists the participants' relationship and identity positioning, and influences their social, academic, and career paths in Japan.